Characterization of iron ore with Al2O3 as oxygen carrier in Chemical Looping Combustion (CLC) - Afandi N.F.; Manap A.; Mahalingam S.; Danial A. (Institute of Physics Publishing, 2023)
Alumina; Aluminum oxide; Ball milling; Carbon; Crystallite size; Fluidized bed combustion; Hematite; Iron research; Milling (machining); Nanostructured materials; Oxygen; Particle size; Scanning electron microscopy; X ray diffraction; Carbon Formation; Chemical-looping combustion; Elemental compositions; Energy dispersive x-ray; Fe-based oxygen carriers; High reactivity; Research focus; Small particle size; Iron ores